ACCOUNTING FROM AN ISLAMIC PERSPECTIVE: BRIDGING SHARIAH VALUES AND MODERN FINANCIAL REPORTING - Raya Puspita Sari Hasibuan; Putri Syuhada; Nuraini Nuraini (CV Visionary Raya Sakti, 2026)
Research Objectives: This study aims to explore accounting from an Islamic perspective by examining how Shariah values can be integrated into modern financial reporting practices. It seeks to analyze the relevance of key Islamic principles—such as accountability (amanah), justice (‘adl), transparency (shafafiyyah), and social responsibility (maslahah)—and assess their potential to complement and enhance contemporary accounting frameworks. Design/ Methodology / Approach Research: The study adopts a qualitative research design using a conceptual and normative approach. It relies on secondary data collected through a systematic literature review of academic journals, books, conference proceedings, and regulatory frameworks, including standards such as IFRS, AAOIFI, and IFSB. Data analysis is conducted using:Content analysis to identify key Shariah principles in accounting, Comparative analysis to examine similarities and differences between Islamic accounting and conventional financial reporting, To ensure validity, the study applies triangulation by integrating insights from multiple credible sources. Research Results: The findings indicate that:Islamic accounting extends beyond technical financial measurement to include ethical, social, and spiritual accountability, emphasizing responsibility not only to stakeholders but also to God, Core Shariah values such as justice, trust, transparency, and social welfare provide a broader and more holistic framework compared to conventional accounting, There are significant areas of convergence between Islamic accounting and modern developments such as sustainability reporting, ESG, and corporate governance. However, challenges remain, including: Lack of standardized Shariah-based accounting frameworks, Limited disclosure of Shariah-specific elements (e.g., zakat, non-halal income), Dominance of shareholder-oriented objectives in conventional accounting.​ Implications of Research Results: The study implies that integrating Shariah values into modern financial reporting can: Enhance the credibility, ethical integrity, and legitimacy of financial statements, Promote a more holistic and value-driven accounting system that incorporates moral and social dimensions, Support the development of hybrid reporting frameworks that balance global standards with Shariah compliance, For practitioners and policymakers, the findings highlight the importance of developing accounting standards that incorporate ethical, social, and religious considerations while maintaining comparability and regulatory compliance.